Efficacy of quinone outside inhibitors and demethylation inhibitors fungicides against false smut of rice (Oryza sativa) - KUMAR, UDAY; KUMAR, AMARENDRA; AZAD, C S; KUMAR, SANJEEV; KUMAR, RAKESH (The Indian Journal of Agricultural Sciences, 2023)
The present study was carried out at research farm of Bihar Agricultural University, Bhagalpur, Bihar during rainy (kharif) season of 2018–19 and 2019–20 to study the efficacy of four quinone outside inhibitors, demethylation inhibitors and benzimidazole group of fungicides, viz. trifloxystrobin 25% + tebuconazole 50% wg, flusilazole 25% + carbendazim 12.5% se, azoxystrobin 18.2% + difenoconazole 11.4% sc and azoxystrobin 11% + tebuconazole 18.3% W/W at different growth stage of rice (Oryza sativa L.), i.e. booting stage (BS), 50% flowering stage (FS) and 100% flowering stage. Among them, trifloxystrobin 25% + tebuconazole 50% wg @1 g/litre at 50% flowering stage was found superior in minimizing the per cent of disease infection. The number of infected tillers/m2 (18.33 and 13.33), number of smut balls/panicle (1.96 and 1.80), smut balls per panicle (0.48% and 0.51%), disease incidence (5.22%and 3.71%) and disease severity (2.86% and 1.78%) respectively were observed in trifloxystrobin 25% + tebuconazole 50% wg @1 g/litre at 50% flowering stage as compared to control. Out of the tested fungicides, trifloxystrobin 25% + tebuconazole 50% wg was found significantly superior in terms of reducing the infection with highest grain yield (90.58 q/ha) and thereby the grain yield upto 43.05% when it was sprayed at 50% flowering stage of crop @1 ml/litre under the field condition in both years. Hence, it is concluded that, trifloxystrobin 25% + tebuconazole 50% wg belonging to two different chemical family group with broad mode of action fungicide significantly (P